Impact of Tenofovir-Based Pre-exposure Prophylaxis on Biomarkers of Bone Formation, Bone Resorption, and Bone Mineral Metabolism in HIV-Negative Adults. (28th July 2019) - Nickolas, Thomas L; Yin, Michael T; Hong, Ting; Mugwanya, Kenneth K; Branch, Andrea D; Heffron, Renee; Ramalho, Janaina; Nandakumar, Renu; Dworakowski, Elzbieta; Wanga, Valentine; Mugo, Nelly R; Ronald, Allan; et al.
Abstract: Background: Pre-exposure prophylaxis (PrEP) with emtricitabine (FTC)/tenofovir disoproxil fumarate (TDF) reduces the risk of HIV seroconversion but may promote bone mineral density (BMD) decline. The mechanisms of BMD decline with FTC/TDF remain unclear, and studies in HIV-positive individuals have been confounded by the effects of HIV and concomitant antiretroviral medications. We evaluated the impact of FTC/TDF on biomarkers of bone remodeling and bone mineral metabolism in HIV-negative men and women enrolled in the Partners PrEP Study. Methods: In a random sample of HIV-negative participants randomized to FTC/TDF PrEP (n = 50) or placebo (n = 50), serum parathyroid hormone (PTH), bone biomarkers (C-telopeptide, procollagen 1 intact N-terminal propeptide, and sclerostin), and plasma fibroblast growth factor 23 were measured at baseline and month 24, and the percentage change was compared between groups. In a complementary analysis, we compared the change in biomarkers between participants with and without a 25% decline in glomerular filtration rate (GFR) on FTC/TDF. Results: Baseline characteristics were similar between the groups (median age, 38 years; 40% women). Vitamin D insufficiency was common, but baseline GFR and PTH were in the normal range. We observed a significantly greater percent increase in serum C-telopeptide in participants randomized to FTC/TDF vs placebo ( P = .03), suggesting an increase in bone remodeling. We observed no differences in the other biomarkers, or in a separate analysis comparing participants with and without a decline in GFR. Conclusions: Increased bone remodeling may mediate the BMD decline observed with tenofovir-containing PrEP and antiretroviral therapy, independent of a TDF-mediated decrease in kidney function.